Vampire diaries : The Hunters : Phantom / [book 8] - Smith, L. J., 1965- (Lisa Jane) (Hodder Children's Books, 2011)
Saving Fell´s Church from evil has come at a price: Damon Salvatore´s life. Now that he´s gone, Elena and Stefan can finally be together. So why can´t Elena stop dreaming of Damon? As Elena´s feelings for Damon grow, a new darkness is threatening to kill Elena and everyone she loves...